Efficacy and safety of ombitasvir/paritaprevir/ritonavir and ribavirin for chronic hepatitis patients infected with genotype 2a in Japan. Issue 4 (2nd January 2019) - Atsukawa, Masanori; Tsubota, Akihito; Toyoda, Hidenori; Takaguchi, Koichi; Nakamuta, Makoto; Watanabe, Tsunamasa; Tada, Toshifumi; Tsutsui, Akemi; Ikeda, Hiroki; Abe, Hiroshi; Kato, Keizo; Uojima, Haruki; et al.
Abstract : Aim: The aim of this study was to evaluate the efficacy and safety of community‐based ombitasvir/paritaprevir/ritonavir plus ribavirin therapy for non‐cirrhotic patients with hepatitis C virus (HCV) genotype 2a infection in a real‐world setting. Methods: Patients with HCV genotype 2a infection were enrolled in this study and received the therapy for 16 weeks at 11 specialized centers in Japan between October 2016 and July 2017. Among the 98 patients participating in the study, four patients were excluded because of the presence of cirrhosis and/or genotype 2b infection. The remaining 94 patients were subjected to the analysis. Results: The patients consisted of 38 women and 56 men, with a median age of 63 years. The rate of sustained virologic response (SVR) was 97.9%. The SVR rates were similar between patients with and without ribavirin dose reduction (96.0% vs. 98.6%, respectively). Of the two patients in whom treatment failed, one patient completed the treatment but relapsed at 4 weeks post‐treatment, whereas the other did not show virologic response and therefore discontinued treatment at week 9. At baseline, both patients had non‐structural protein (NS)5A resistance‐associated substitution (RAS) L31M but no NS3 RAS. At the time of relapse, the patient had NS5A RAS F28S. At the premature treatment discontinuation, the non‐responder had NS3 RAS D168V and NS5A RAS T24S. Ribavirin‐induced anemia was the most frequent adverse event. Conclusion: Community‐based, 16‐week, ombitasvir/paritaprevir/ritonavir plus ribavirin therapy was highly efficacious and safe in non‐cirrhotic patients with HCV genotype 2a infection in a real‐world setting.